The black widow - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2016)
Gabriel Allon, the art restorer, spy, and assassin is poised to become the chief of Israel<U+2019>s secret intelligence service. But on the eve of his promotion, events conspire to lure him into the field for one final operation. ISIS has detonated a massive bomb in the Marais district of Paris, and a desperate French government wants Gabriel to eliminate the man responsible before he can strike again.